Development of an enzyme-linked immunosorbent assay for detecting Campylobacter hepaticus specific antibodies in chicken sera – a key tool in Spotty Liver Disease screening and vaccine development. Issue 6 (1st November 2020) - Muralidharan, Chithralekha; Anwar, Arif; Wilson, Timothy B.; Scott, Peter C.; Moore, Robert J.; Van, Thi Thu Hao
ABSTRACT: Spotty Liver Disease (SLD) is an emerging disease of serious concern in the egg production industry, as it causes significant egg loss and mortality in layer hens. The causative agent is a newly identified Gram-negative bacterium, Campylobacter hepaticus, and knowledge about C. hepaticus pathogenesis and the potential for vaccine development is still in its infancy. Current detection methods for SLD, such as PCR and culturing, only detect an active infection and will not give any indication of a past infection from which the bacteria have been cleared. An immunological assay, on the other hand, can provide information on previous infections and therefore is crucial in vaccine development against SLD. In the present study, we have developed the first immunoassay capable of detecting C. hepaticus -specific antibodies present in the sera of infected birds. The assay uses C. hepaticus total protein extract (TPE) as the antigen coating on enzyme-linked immunosorbent assay (ELISA) plates. The cross reactivity of C. hepaticus antibodies with closely related C. jejuni and C. coli antigens was successfully overcome by pre-absorbing the sera using C. jejuni cell extracts. The assay was validated using sera samples from both naturally- and experimentally-infected birds, birds vaccinated with formalin-killed bacteria, and serum samples from SLD-negative birds (control group). The optimized ELISA assay had 95.5% specificity and 97.6% sensitivity. The immunoassay provides a useful tool for monitoring the exposure of poultry flocks to C. hepaticus infection and can be used to direct and support vaccine development. HIGHLIGHTS The first immunoassay developed for Spotty Liver Disease (SLD). A useful method for detecting C. hepaticus -specific antibodies in birds. Highly specific (95.5%) and sensitive (97.6%) assay. A key tool for use in epidemiological studies and vaccine development.